2007
DOI: 10.1007/s10162-007-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of Hearing by Simultaneous Mutation of Na,K-ATPase and NKCC1

Abstract: Although drug-induced and age-related hearing losses are frequent otologic problems affecting millions of people, their underlying mechanisms remain uncertain. The inner ear is exclusively endowed with a positive endocochlear potential (EP) that serves as the main driving force for the generation of receptor potential in hair cells to confer hearing. Deterioration of EP leads to hearing loss or deafness. The generation of EP relies on the activity of many ion transporters to establish active potassium (K + ) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 46 publications
0
38
1
Order By: Relevance
“…Although homozygous deletion of either NKAα1 or NKAα2 is lethal at birth, heterozygous deletions are viable (Moseley et al 2007). Despite normal cochlear morphology, NKAα1 +/− and NKAα2 +/− mice show reductions in the endocochlear potential and progressive, age-dependent hearing loss (Diaz et al 2007). A possible neuronal contribution to hearing loss in these mice has not been excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Although homozygous deletion of either NKAα1 or NKAα2 is lethal at birth, heterozygous deletions are viable (Moseley et al 2007). Despite normal cochlear morphology, NKAα1 +/− and NKAα2 +/− mice show reductions in the endocochlear potential and progressive, age-dependent hearing loss (Diaz et al 2007). A possible neuronal contribution to hearing loss in these mice has not been excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Absorbed K ϩ may leak in the perilymph through background K ϩ channels that remain to be characterized. However, since transitional cells still express NKCC1 and Na/K-ATPase, they may mask their secreting potential by means of a currently unknown mechanism (indicated with a question mark ing the cochlear endolymph (Diaz et al, 2007). Last, coadministration of ouabain and bumetanide failed to increase [K ϩ ]ec inhibition, indicating that the pump drives NKCC1 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In this and other mouse models we have examined, we have interpreted reduced marginal cell density as an indication that critical marginal cell functions in generating the EP are impaired. We suppose-but have yet to show-that fewer, larger, marginal cells maintain fewer critical pumps, transporters, and channels , or alter the critical 'stoichiometry' of these among strial cell types (Diaz et al 2007). We have not proposed or observed that marginal cell degeneration leaves exposed intermediate cells or alters the ion barrier of scala media.…”
Section: Loss Of Outer Sulcus Cells In Cba/cajmentioning
confidence: 98%